Hak Asasi Manusia dalam Perspektif Hukum Islam - Muhammad, Adji Suradji (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Islam is the doctrine that governs all human life is a beautiful early rapid. One of the issues currentlybeing faced by Islam is associated with Azaz human rights (human rights). United Nations Charter onHuman Rights has recommended to promote and fight for human rights and freedom for all human beings,without distinction as to race, sex, language or religion. Human rights (Human Rights) is a conceptof modern political ethics with the idea of appreciation and respect for basic human and humanity.Islam is not contradicting the values of human rights, but there needs to be synchronization values areacceptable by Islam and which are unacceptable to Islam. Freedom of the freest in the association of oppositionfrom Islam. So it is related to the kind of relationship both by men and by women. Therefore,the existing values in the concept of human rights is sejelan with Islamic values such as freedom to worshipaccording to their beliefs. Synchronization of the values championed by the pro-human rights withIslamic values should be done so that there is no longer conflict between fighters Ham with adherents ofIslam.